Digital Payments, Social Media, and Mental Accounting: Determinants of Generation Z’s Consumption Behavior - Asnawir Asnawir; Nurhaedah Nurhaedah; Baso Sardjan; A. Muh. Anzhari; Revoldai Agusta; Andi Fajriansyah (SEAN Institute, 2026)
Advances in financial technology and the penetration of social media have transformed the consumption patterns of Generation Z, a group of digital natives in Indonesia. This study aims to analyze the influence of payment digitization, mental accounting, and social media lifestyle exposure on the consumption behavior of Generation Z, as well as to examine the role of financial self-efficacy as a moderating variable in these three relationships. The study employed a quantitative approach using a survey of 109 Generation Z respondents aged 17–28 in Makassar, selected through purposive sampling. Data were collected via an online questionnaire using a five-point Likert scale and analyzed using Partial Least Squares-based Structural Equation Modeling (SEM-PLS) with the assistance of SmartPLS. The results indicate that payment digitalization, mental accounting, and exposure to social media lifestyles have a positive and significant effect on Generation Z’s consumer behavior. Financial self-efficacy was found to significantly weaken the influence of payment digitalization and mental accounting on consumer behavior; however, it failed to weaken the influence of exposure to social media lifestyles, as lifestyle factors proved to be more dominant than an individual’s capacity to manage finances. These findings have important implications for the development of digital financial literacy strategies that target psychological and social aspects not merely the improvement of financial knowledge in order to protect the younger generation from the risks of excessive digital consumerism.